C-CORE : uma Ferramenta de programação para construção e reuso de componentes - Souza Neto, Raphael Marcilio de (Universidade Federal de São Carlos, 2005)
The Software Development contains several activities that are not always supported by tools that aid the Software Engineer and automate great part of his activities. Different researches have been accomplished and many resources have been spent aiming to construct tools that support the Software Development Process. Among these tools, stand out those that support project and implementation activities, and that are integrated with tools that support other activities of the software construction process. With those tools, it can be obtained a larger consistence of the results that are produced along the whole software development cycle. Another important point of the development process is related to obtain a software with better quality and less cost. One of the areas that is highlighted in the software production with quality and less cost, is those that researches the software components reuse. Thus, the Software Component Oriented Programming Tools integrated with modeling tools that aim mainly to improve the software productivity based on reuse is standing out. Motivated by these ideas, this work presents a tool denominated C-CORE, that supports the project and implementation of components and their applications integrated with other modeling tool, denominated MVCASE.
Keywords: Desenvolvimento de software baseado em componentes; Ferramenta de desenvolvimento; Catalysis/UML; Componentes de software; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO